Pengenalan Software Appy Pie Berbasis Android untuk Bahan Pembelajaran di TKQ Al-Falah Depok - Khotijah, Siti; Juliana; Driyani, Dewi; Hartanti, Dian (Journal Of Computer Science Contributions (JUCOSCO), 2025)
TKQ AL-Falah is located in Pancoran Mas Depok sub-district, a place of learning for kindergarten children, where currently the implementation of teaching and learning is still using traditional and manual methods which is less interesting teaching materials. It is not utilized on android in the teaching and learning process. Therefore, a form of learning is needed that provides a new color, by utilizing Appy Pie software which has easy-to-use features. By utilizing Appy Pie software, teachers can easily provide learning media to be more fun and diverse according to student needs. In this community service, the aim is to provide an introduction to Appy pie software which can later be applied using android to help teachers at TKQ in creating interesting and interactive teaching materials.